The Topology of Marble: The Matter of Estremoz’s Built Heritage - Cidalia Ferreira Silva; Luis Duarte Esteves (Joelho)
This paper addresses built heritage from the perspective of marble as a cross-scale legacy between distant and close places. Through Estremoz marble we make visible that heritage is not only a static element to preserve but a matter continuously in motion across time and space. Topology of marble brings to the fore this awareness of seeing the interconnection between its geological formation, the extraction and the constructive processes, in a multiplicity of cycles still in transformation.